2022
DOI: 10.3390/joitmc8010023
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Digital Marketing Influences on Sales for B2B Start-Ups in South Asia

Abstract: South Asia has seen a digital revolution in recent years. The number of persons who use the internet has risen drastically. They use it for shopping, social media and online sales. However, there exists a literature gap as far as the effect of outbound digital marketing in B2B markets is concerned. The research builds a model based on brand and consumer interactions in Indian B2B markets using a vector autoregressive model to systemically analyze the cost and outcome of digital marketing efforts by the start-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
9
1
2
Order By: Relevance
“…This assertion is corroborated by a prior investigation conducted by Bowden and Mirzaei (2021), which posited that online brand communities exert a substantial and augmenting influence on the association between self-brand connections and engagement. The findings of Hawaldar et al (2022) demonstrate a significant correlation between digital media and sales, indicating that outbound marketing strategies, particularly word-of-mouth promotion, play a crucial role in establishing a brand's image as it proliferates across various social media platforms.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This assertion is corroborated by a prior investigation conducted by Bowden and Mirzaei (2021), which posited that online brand communities exert a substantial and augmenting influence on the association between self-brand connections and engagement. The findings of Hawaldar et al (2022) demonstrate a significant correlation between digital media and sales, indicating that outbound marketing strategies, particularly word-of-mouth promotion, play a crucial role in establishing a brand's image as it proliferates across various social media platforms.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Given that, the study specifically highlighted the growing importance of social media as an effective marketing tool, which was and is being used vigorously since the pandemic began as it positively impacted the consumer decision-making process. Hawaldar et al (2022) observed that the strategies of digital marketing and customer interaction were the same all over southern Asia but its effect varied from country to country. Other than this the results showed that digital marketing has a huge impact on sales and outbound marketing, especially word of mouth, greatly influenced the brand image as it spreads all across social media.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This digital marketing strategy also applies for destination branding, as the internet is the first choice to seek information about destinations (Khan et al , 2022; Garbarova and Vartiak, 2022). Recently, South Asia is focusing on digital marketing activities and observing an evident growth in their economies and witnessing a rise in social media usage (Hawaldar et al , 2022).…”
Section: Research Contextmentioning
confidence: 99%